HAK WARIS ANAK ANGKAT DALAM HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Rahman, Fathor; Fida , Imanuddin Abil (LPPM STAI Muhammadiyah Probolinggo, 2023)
This study examines children's rights from the perspective of Islamic law and positive law in Indonesia. Utilizing a deskriptif qualitative methodology, this study aims to analyze the legal rights of children in conflict as well as the differences between Islamic and positive Indonesian law on the custody of children. The deskriptif method of quantitative analysis is used to provide a comprehensive picture of the differences between Islamic and positive Indonesian law concerning the rights of minors. This study provides a more comprehensive understanding of the application of law concerning the guardianship of adopted children, which can serve as a foundation for longer-term legislative development in Indonesia. Keywords: Inheritance Rights of Adopted Children, Islamic Law, Positive Law in Indonesia